Prognostic significance of hedgehog signaling network‐related gene expression in breast cancer patients. Issue 5 (8th January 2021) - Kuehn, Julia; Espinoza‐Sanchez, Nancy Adriana; Teixeira, Felipe C. O. B.; Pavão, Mauro S. G.; Kiesel, Ludwig; Győrffy, Balázs; Greve, Burkhard; Götte, Martin
Abstract: Breast cancer continues to be a serious public health problem. The role of the hedgehog pathway in normal development of the mammary gland as well as in carcinogenesis and progression of breast cancer is the subject of intense investigation, revealing functional interactions with cell surface heparan sulfate. Nevertheless, its influence on breast cancer prognosis, and its relation to specific sulfation motifs in heparan sulfate have only been poorly studied in large patient cohorts. Using the public database KMplotter that includes gene expression and survival data of 3951 patients, we found that the higher expression of SHH, HHAT, PTCH1, GLI1, GLI2, and GLI3 positively influences breast cancer prognosis. Stratifying patients according to the expression of hormone receptors, histological grade, lymph node metastasis, and systemic therapy, we observed that GLI1, GLI2, and GLI3 expression, as well as co‐expression of SHH and ELP1 were associated with worse relapse‐free survival in patients with HER2‐positive tumors. Moreover, GLI1 expression in progesterone receptor‐negative tumors and GLI3 expression in grade 3 tumors correlated with poor prognosis. SHH,  in a panel of cell lines representing different breast cancer subtypes, and HHAT, PTCH1, GLI1, GLI2, and GLI3 were mostly expressed in cell lines classified as HER2‐positive and basal‐like. Expression of SHH, HHAT, GLI2, and GLI3 was differentially affected by overexpression of the heparan sulfate sulfotransferases HS2ST1 and HS3ST2 in vitro. Although high HS2ST1 expression was associated with poor prognosis in KMplotter analysis, high levels of HS3ST2 were associated with a good prognosis, except for ER‐positive breast cancer. We suggest the GLI transcription factors as possible markers for the diagnosis, treatment, and prognosis of breast cancer especially in HER2‐positive tumors, but also in progesterone receptor‐negative and grade‐3 tumors. The pathway interaction and prognostic impact of specific heparan sulfate sulfotransferases provide novel perspectives regarding a therapeutical targeting of the hedgehog pathway in breast cancer. Abstract : The hedgehog pathway plays an important role during mammary gland development and breast cancer pathogenesis. In this study, we establish general and subtype‐specific prognostic values for selected hedgehog pathway constituents in breast cancer, and provide a link to heparan sulfate. The pathway interaction and prognostic impact of specific heparan sulfate sulfotransferases provide novel perspectives regarding a therapeutical targeting of the hedgehog pathway in breast cancer.